Dietary inflammatory potential, oxidative balance score, and risk of breast cancer: Findings from the Sister Study. Issue 3 (27th April 2021) - Park, Yong‐Moon Mark; Shivappa, Nitin; Petimar, Joshua; Hodgson, M. Elizabeth; Nichols, Hazel B.; Steck, Susan E.; Hébert, James R.; Sandler, Dale P.
Abstract: Diet, inflammation, and oxidative stress may be important in breast carcinogenesis, but evidence on the role of the inflammatory and prooxidative potential of dietary patterns is limited. Energy adjusted‐Dietary Inflammatory Index (E‐DII™) and dietary oxidative balance score (D‐OBS) were calculated for 43 563 Sister Study cohort participants who completed a Block 1998 food frequency questionnaire at enrollment in 2003–2009 and satisfied eligibility criteria. D‐OBS was validated using measured F2 ‐isoprostanes and metabolites. High E‐DII score and low D‐OBS represent a more proinflammatory and prooxidant diet, respectively, and associations of quartiles of each index with breast cancer (BC) risk were estimated using multivariable Cox proportional hazards regression. There were 2619 BCs diagnosed at least 1 year after enrollment (mean follow‐up 8.4 years). There was no overall association between E‐DII and BC risk, whereas there was a suggestive inverse association for the highest vs lowest quartile of D‐OBS (HR 0.92 [95% CI, 0.81‐1.03]). The highest quartile of E‐DII was associated with risk of triple‐negative BC (HR 1.53 [95% CI, 0.99‐2.35]). When the two indices were combined, a proinflammatory/prooxidant diet (highest tertile of E‐DII and lowest tertile of D‐OBS) was associated with increased risk for all BC (HR 1.13 [95% CI, 1.00‐1.27]) and for triple‐negative BC (1.72 [95% CI, 1.10‐2.70]), compared to an antiinflammatory/antioxidant diet (lowest tertile of E‐DII and highest tertile of D‐OBS). Diets with increased inflammatory potential and reduced oxidative balance were positively associated with overall and triple‐negative BC. Abstract : What's new? Inflammation and oxidative stress may promote breast and other cancers. The role of diet is still uncertain, however. In this study, using the Dietary Inflammatory Index (DII™) and dietary oxidative‐balance scores (D‐OBS), the authors found that diet may indeed be associated with an increased risk of both overall and especially triple‐negative breast cancer. The greatest risk was seen in diets with the poorest proinflammatory and prooxidative scores combined. These results suggest that modifying dietary lifestyle factors may help reduce the risk of breast cancer.